Visual memory in musicians and non-musicians - Rodrigues, Ana Carolina; Loureiro, Maurício; Caramelli, Paulo (Frontiers in Human Neuroscience, 2014)
Many investigations have reported structural, functional and cognitive changes in the brains of musicians, which occur as a result of many years of musical practice. We aimed to investigate if intensive, long-term musical practice is associated with improved visual memory ability. Musicians and non-musicians, who were comparable in age, gender and education, were submitted to a visual memory test. The test consisted of the presentation of 4 sets of stimuli, each one containing 8 figures to be memorized. Each set was followed by individual figures and the subject was required to indicate if each figure was or was not present in the memorized set, by pressing the corresponding keys. We divided the test in two parts, in which the stimuli had greater or reduced semantic coding. Overall, musicians showed better performance on reaction times, but not on accuracy. An additional analysis revealed no significant interaction between group and any part of the test in the prediction of the outcomes. When simple reaction time was included as covariate, no significant difference between groups was found on reaction times. In the group of musicians, we found some significant correlations between variables related to musical practice and performance in the visual memory test. In summary, our data provide no evidence of enhanced visual memory ability in musicians, since there was no difference in accuracy between groups. Our results suggest that performance of musicians in the visual memory test may be associated with better sensorimotor integration, since although they have presented shorter reaction times, such effect disappeared when taken in consideration the simple reaction time test. However, given existing evidence of associations between simple reaction time and cognitive function, their performance in the visual memory test could also be related to enhanced visual attention ability, as has been suggested by previous studies, but this hypothesis deserves more investigation.